Re-Examining the Value of UK University Business Studies Courses for Post- Graduation Nepalese Graduates - Gilliam, Paul H.; Pratt-Adams, Simon; J. P. Kerrigan, Mark (Journal of Education and Research, 2020)
This research analyses the reflections of post-graduation Nepalese Business Studies undergraduate and postgraduate graduates from UK universities. It follows their return to Nepal, where the graduates were facing a scarcity of employment opportunities. The primary research was undertaken at a time when UK universities were facing increasing competition to recruit international students and numbers of Nepalese students choosing the UK were decreasing. The mixed methods research was based primarily on semi-structured interviews in Nepal with twenty-three Nepalese graduates, their Nepalese employers and Nepalese education consultancies. Data were analysed using the five systems model of Bronfenbrenner (1979) and Trompenaars and Hampden-Turner’s (2012) Intercultural Awareness Profiling. Although the overall expectations of Nepalese students and employers towards UK higher education remained positive, results indicated a lowering estimation of the quality and reputation of UK universities and increasing Nepalese University and regional competition. The outcomes make a further contribution to the knowledge of why Nepalese students choose overseas higher education but why Nepalese employers are struggling to see clear benefits from employing UK educated Nepalese business graduates.